2021
DOI: 10.1186/s12889-021-11833-2
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal variation in tuberculosis incidence and risk factors for the disease in a region of unbalanced socio-economic development

Abstract: Background Previous research pointed to a close relationship between the incidence of tuberculosis (TB) in aging populations and socio-economic conditions, however there has been lack of studies focused on a region of unbalanced socio-economic development. The aim of this paper is to explore the spatio-temporal variation in TB incidence and examine risk determinants of the disease among aging populations in a typical region. Methods Data on TB-regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 38 publications
0
10
0
3
Order By: Relevance
“…A subsequent prospective cohort study reported high TB incidence rates, [ 21 ] highlighting the need to prioritise older adults in the TB response. TB-related mortality was also more prevalent among older adults [ 19 ] concentrated in China’s Central and South-Eastern regions, [ 22 ] among lower-income residents from rural areas and in those with comorbidities [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…A subsequent prospective cohort study reported high TB incidence rates, [ 21 ] highlighting the need to prioritise older adults in the TB response. TB-related mortality was also more prevalent among older adults [ 19 ] concentrated in China’s Central and South-Eastern regions, [ 22 ] among lower-income residents from rural areas and in those with comorbidities [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, economically undeveloped regions have a lower population density but relatively abundant per capita medical resources. However, the uneven development of regional economy contributes to spatial differences in TB incidence in the study area [ 37 39 ], due to limitations imposed by the natural environment, educational level, and customs, TB prevention and control efforts may not yield immediate results in these regions [ 26 ]. Previous studies have revealed associations between TB and per capita GDP, poverty, living standards, and malnutrition [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The resident population data of each district and county were from the Statistical Yearbook published by the Chongqing Municipal Bureau of statistics. The four variables of social economy and environment were considered as followings: (1) Environment: including PM 10 (μg/m 3 ), SO 2 (μg/m 3 ), and NO 2 (μg/m 3 ) [ 11 , 17 , 18 ]; (2) Population characteristics: including population density (PD)(people/km 2 ), urbanization rate (UR)(%) and proportion of people engaged in agriculture(%)(PEIA); (3) Economic level: including per capita GDP (1000 yuan)(PGDP), disposable income of urban residents (1000 yuan)(DIUR), disposable income of rural residents (1000 yuan)(DIRR) and the number of low-income group per 1000 non-agricultural households (LINA per 1000 persons) [ 19 ]. The above data were obtained from the Statistical Yearbook published by the Chongqing Municipal Bureau of statistics and the environmental statistical bulletin issued by the Chongqing Municipal Bureau of ecological environment.…”
Section: Methodsmentioning
confidence: 99%